Abrocoma schistacea (Rodentia: Abrocomidae). (20th August 2015) - Taraborelli, Paula A.; Sassi, Paola L.; Dacar, María A.; Moreno, Pablo; Ojeda, Ricardo A.
Abstract: Abrocoma schistacea Thomas, 1921 is an abrocomid rodent commonly known as the Sierra del Tontal chinchilla rat. This medium-sized chinchilla rat is a rock specialist that inhabits the pre-Andean foothills of southern San Juan Province (Argentina) within an elevation range of 1, 100–2, 900 m. Its saxicolous specializations include padded feet with leathery tubercles on the pads. Incisors are large and orthodont; molariform teeth appear broad. A. schistacea is a creosotebush dietary specialist that can be distinguished from other chinchilla rats by living in groups of 3–4 individuals. This species is categorized as of low conservation concern in Argentina but is currently listed as "Data Deficient" by the International Union for Conservation of Nature and Natural Resources.